2019
DOI: 10.1051/epjn/2019026
|View full text |Cite
|
Sign up to set email alerts
|

Breed-and-burn fuel cycle in molten salt reactors

Abstract: The operation of a reactor on an open but self-sustainable cycle without actinide separation is known as breed-and-burn. It has mostly been envisioned for use in solid-fueled fast-spectrum reactors such as sodium-cooled fast reactors. In this paper the applicability of breed-and-burn to molten salt reactors is investigated first on a cell level using a modified neutron excess method. Several candidate fuel salts are selected and their performance in a conceptual three-dimensional reactor is investigated. Chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The BNB fuel cycle differs from the once-through fuel cycle of fluorine salt. The BNB can realize the long-term selfsustaining burn of the fuel without using online chemical reprocessing and supply of enriched fuel [29]. Therefore, since a long-term self-sustaining burn can be achieved by adding only 238 U for chlorine salt reactors when the neutron loss ratio is low, the natural uranium burnup difference is orders of magnitude higher than that of the fluorine reactor or the chlorine reactor with a high neutron loss ratio, so it is not shown in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The BNB fuel cycle differs from the once-through fuel cycle of fluorine salt. The BNB can realize the long-term selfsustaining burn of the fuel without using online chemical reprocessing and supply of enriched fuel [29]. Therefore, since a long-term self-sustaining burn can be achieved by adding only 238 U for chlorine salt reactors when the neutron loss ratio is low, the natural uranium burnup difference is orders of magnitude higher than that of the fluorine reactor or the chlorine reactor with a high neutron loss ratio, so it is not shown in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, BNB fuel cycle mode is not possible for fluorine salts in both thermal and fast spectra. It is worth noting that in solid fuel fast reactors, the fuels at different burnup moments can be combined and split arbitrarily, so it is theoretically possible to establish the neutron generation and absorption equilibrium at any moment, but in molten salt reactors it is difficult to split the molten salt once it is combined, so it is difficult to separate the fuels under deep burnup, which makes the neutron equilibrium too ideal and the actually obtained burnup will be much lower than the theoretical analysis, as studied in more detail by Hombourger et al [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of codes and methods are usually employed for this purpose; ORIGEN [5], SCALE [1,3,18], SERPENT [20,21], perturbation theory [13], and linear chain method [35,36] are more popular, among others. The neutron spectrum of the reactor has different effects on the core inventory of MSRs and needs to be evaluated individually [5,14]. For small-scale molten salt reactors, the difference in fuel utilization under thermal and fast spectra (both iMAGINE and EVOL) is small.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of high actinide concentration is of particular concern, as electrorefiners typically operate at about 5-10 wt% UCl 3 , 25 while MSRs may have up to about 40 mol% (80 wt%) UCl 3 . 26 There has been a progression of pushing the composition limits for study of U and Pu in electrorefiner salts over the last 20 years. Notably, Iizuka et al first reported U and Pu concentration measurement via online electrochemical methods (SWV and NPV) in LiCl-KCl.…”
mentioning
confidence: 99%